Reviving the Ganges water machine: why? - Amarasinghe, Upali A.; Muthuwatta, Lal P.; Surinaidu, L.; Anand, Sumit; Jain, S.K. (Copernicus GmbH, 2015)
The Ganges River Basin may have a major pending water crisis. Although the basin has abundant surface water and groundwater resources, the seasonal monsoon causes a mismatch between supply and demand as well as flooding. Water availability and flood potential is high during the 3–4 months of the monsoon season. Yet, the highest demands occur during the 8–9 months of the non-monsoon period. Addressing this mismatch requires substantial additional storage for both flood reduction and improvements in water supply. Due to hydrogeological, environmental, and social constraints, expansion of surface storage in the Ganges River Basin is problematic. A range of in- terventions that focus more on the use of subsurface storage (SSS), and on the acceleration of surface–subsurface water exchange, have long been known as the “Ganges Water Machine”. One approach for providing such SSS is through additional pumping prior to the onset of the monsoon season. An important necessary condition for creating such SSS is the degree of unmet water demand. This paper highlights that an unmet water demand ranging from 59 to 119 Bm3 exists under two different irrigation water use scenarios: (i) to increase Rabi and hot weather season irrigation to the entire irrigable area, and (ii) to provide Rabi and hot weather season irrigation to the entire cropped area. This paper shows that SSS can enhance water supply, and provide benefits for irrigation and other water use sectors. In addition, it can buffer the inherent variability in water supply and mitigate extreme flooding, especially in the downstream parts of the basin. It can also increase river flow during low-flow months via baseflow or enable the re-allocation of irrigation canal water. Importantly, SSS can mitigate the negative effects of both flooding and water scarcity in the same year, which often affects the most vulnerable segments of society – women and children, the poor and other disadvantaged social groups.